A water-induced self-assembly approach to 3D hierarchical magnetic MXene networks for enhanced microwave absorption. Issue 1 (8th December 2022) - Xu, Jian; Ma, Wenjun; He, Peng; Zhou, Yukang; Liu, Xiaoyun; Chen, Yi; Zuo, Peiyuan; Zhuang, Qixin
Abstract : A novel water-induced self-assembly method is developed for constructing ultrafine magnetic nanocrystal@carbon@MXene with continuous interfaces and high-density magnetic coupling networks. Abstract : Three-dimensional (3D) network structures assembled from two-dimensional (2D) MXene nanomaterials hold enormous potential for microwave absorption (MA) due to strong dielectric loss ability. However, the uncontrollable oversized conductive paths caused by self-stacking issues and the natural lack of magnetic loss hinder the further MA application of the assembled 3D MXene. Herein, we report a facile water-induced self-assembly method to develop a series of 3D hierarchical magnetic nanocrystal@C@MXene hybrids with tunable network structures. The design of the hierarchical structure can isolate each electromagnetic component, thereby ensuring the efficient synergy of the high-density ultrafine magnetic components and high-loss dielectric components. The resulting massive heterointerfaces greatly enhance the interface polarization and reinforce the dielectric loss capability. Moreover, through control over the MXene load, the size of 3D networks can be precisely regulated to adjust the impedance matching. According to experimental and finite element simulation, all the 3D hierarchical magnetic hybrids were found to possess impressive MA properties. Specifically, ZnFe2 O4 @C@MXene exhibits a minimum reflection loss value of −62.59 dB over an effective absorption bandwidth of 4.42 GHz at a thickness of only 1.33 mm. This work provides a flexible route for constructing 3D hierarchical network materials to realize highly efficient MA performance with thin thickness.